The Federal Commitment to Homelessness Prevention: A Silver Lining of the Economic Crisis. Issue 1 (March 2014) - Colburn, Gregg
<x xml:space="preserve">Abstract</x> In the midst of the 2007–2009 economic crisis, the federal government altered its response to homelessness in significant ways. After years of providing services and support to individuals and families who were homeless, in 2009 the government bolstered its response and for the first time provided significant resources to prevent homelessness. The purpose of this article is to provide an explanation of the significant shift in federal homelessness policy in 2009. The author uses the multiple streams and social construction policy frameworks to analyze the 2009 homelessness policy change. Social, political, and economic changes during the recession provided a unique opportunity to implement policy solutions that were previously unattractive or politically unfeasible. While the economic crisis was a source of broad‐based hardship in the United States, the crisis created unique conditions that contributed to a significant change in federal homelessness policy. The findings of this article are significant for scholars, policymakers, and advocates who seek to promote public policies that benefit vulnerable, oppressed, or marginalized populations.